큐잉 이론을 이용한 DBSW 알고리즘 성능 분석 - 조해성(Hae-Seong Cho) (한국콘텐츠학회 논문지, 6(11), 2006)
WRR scheme was developed for scheduling scheme for guaranteeing bandwidth requirement. In these days, WRR scheme can handle multiple queues straightforwardly by putting a different weight on each queue in order to offer differentiated services such as different bandwidth or delay bound in wireless communication network. Also, WRR algorithm can be implemented efficiently by dynamic binary scheduling wheel(DBSW) architecture. This paper performs the mathematical analysis of the DBSW architecture and compares the results with simulation results. The analysis data and simulation data show that the mathematical analysis developed properly. WRR 기법은 대역을 보장해야 하는 스케줄링 기법으로 개발되었다. 최근에는 무선 통신 네트워크에서 다양한 대역이나 지연과 같은 차등화 된 서비스들을 제공 할 수 있도록 각 큐에 다른 가중치를 지정함으로써 여러 큐들을 직접적으로 관리할 수 있도록 하였다. 또한, WRR 알고리즘은 DBSW 구조에 의해 효율적으로 구현할 수 있다. 본 논문은 WRR 구현의 대표적인 방법인 DBSW 구조의 수학적 분석을 수행하고 분석결과와 시뮬레이션 결과를 비교 분석한다. 분석 데이터와 시뮬레이션 데이터는 수학적 분석이 타당하게 전개되었음을 입증하는 성능 결과를 보여주고 있다.